Differentiated Instruction: Analysis of Elementary School Teachers’ Understanding in Bali Q-Ta School: Pembelajaran Berdiferensiasi: Analisis Pemahaman Guru Sekolah Dasar di Sekolah Bali Q-Ta - Witraguna, Kadek Yudista; Jaya, I Ketut Manik Asta (Universitas Muhammadiyah Sidoarjo, 2024)
Differentiated instruction is implemented to support the application of the Merdeka Curriculum. Teachers need to have a good understanding before implementing differentiated instruction. The study aims to determine and analyze the understanding of elementary school teachers regarding differentiated instruction at Bali Q-Ta School (SD Bali Q-Ta), as well as to identify the constraints in its implementation. The research was conducted using mixed methods. The subjects of this study were all elementary school teachers at SD Bali Q-Ta. Research data was obtained using questionnaires and interviews. The data obtained were analyzed descriptively. Findings indicate that the understanding of elementary school teachers at SD Bali Q-Ta falls into the